The Cloven. Book one - Stein, Garth; Southworth, Matthew (Fantagraphics Books, Inc., 2020)
"The Cloven Book One stars James Tucker, the most successful genetically modified human organism ever created. Conceived in a privately financed, top-secret laboratory on Washington State's Vashon Island, Tucker is a cross between a human and a goat -- a Cloven. Known to his friends as "Tuck", all he wants is to live a normal life as a university student; everything is going fine, until he shows a girl his hoofs...,"--Title page verso.